Techniques utilized in molecular genetics - Lewis, Cecil (Henry Stewart Talks, 2011)
Techniques utilized in molecular genetics, Genetic material separation, DNA isolation, mRNA isolation, Genetic libraries, Cell cultures, DNA amplification, Polymerase Chain Reaction, Molecular cloning, Allele characterization, Gel electrophoresis, Probe hybridization, Real time PCR, RT-PCR: Dissociation curves, RT-PCR: End-point analysis, Dye-terminator DNA sequencing, High throughput DNA sequencing